High-frequency Conductivity of Carbon Nanotubes of Zigzag-configuration - A.V. Korotun; І.М. Titov; Ya.V. Karandas (Журнал нано- та електронної фізики)
The frequency dependences of the surface conductivity of carbon nanotubes of zigzag-configuration have been investigated in the single-electron approximation. The calculations have been performed for nanotubes with semiconductor and metallic conductivity. The influence of chirality on the total conductivity and its individual components have been analyzed.